2012
DOI: 10.5194/acp-12-7557-2012
|View full text |Cite
|
Sign up to set email alerts
|

Summer ammonia measurements in a densely populated Mediterranean city

Abstract: Real-time measurements of ambient concentrations of gas-phase ammonia (NH<sub>3</sub>) were performed in Barcelona (NE Spain) in summer between May and September 2011. Two measurement sites were selected: one in an urban background traffic-influenced area (UB) and the other in the historical city centre (CC). Levels of NH<sub>3</sub> were higher at CC (5.6 ± 2.1 μg m<sup>−3</sup> or 7.5 ± 2.8 ppbv) compared with UB (2.2 ± 1.0 μg m<sup>−3</sup> or 2.9 ± 1.3 ppbv).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…3.2.2, at the investigated site a reduction in both in NO − 3 and SO 2− 4 was observed over the warm season and this may cause a further increase in gasphase NH 3 . It is also interesting to observe that the reaction rate constant of (NH 4 ) 2 SO 4 aerosol formation is similar to the rate constant of NH 4 NO 3 formation (Harrison and Kitto, 1992;Pandolfi et al, 2012;Behera et al, 2013), and both are much higher than the rate constant between NH 3 and HCl (Behera and Sharma, 2012). This issue probably dictates the competition of any of the particulate SO 2− 4 , NO − 3 , and Cl − for the available NH + 4 .…”
Section: Stoichiometry Of (Nhmentioning
confidence: 93%
“…3.2.2, at the investigated site a reduction in both in NO − 3 and SO 2− 4 was observed over the warm season and this may cause a further increase in gasphase NH 3 . It is also interesting to observe that the reaction rate constant of (NH 4 ) 2 SO 4 aerosol formation is similar to the rate constant of NH 4 NO 3 formation (Harrison and Kitto, 1992;Pandolfi et al, 2012;Behera et al, 2013), and both are much higher than the rate constant between NH 3 and HCl (Behera and Sharma, 2012). This issue probably dictates the competition of any of the particulate SO 2− 4 , NO − 3 , and Cl − for the available NH + 4 .…”
Section: Stoichiometry Of (Nhmentioning
confidence: 93%
“…The gas-to-particle conversion processes in ambient atmosphere may produce inorganic ammonium salts of ammonium bisulfate (NH 4 HSO 4 ), ammonium sulfate ((NH 4 ) 2 SO 4 ), (Tsai et al, 2014). It is known that NH 4 HSO 4 or (NH 4 ) 2 SO 4 is preferentially formed among the ammoniumassociated compounds because the affinity of sulfuric acid for NH 3 is much larger than that of nitric acid and hydrochloric acid for NH 3 (Pandolfi et al, 2012;Behera et al, 2013b ) (Behera and Sharma, 2012). The overall relationship between molar concentrations of NH 3 and the corresponding PM 2.5 -bound NH 4 + during the whole field measurement period was shown in Fig.…”
Section: Relationship Between Nh 3 and Ammonium Salts In Pm 25 Overamentioning
confidence: 99%
“…Norman et al (2009) and Meng et al (2011) compared different ammonia analysis methods and found accuracy of the online method is acceptable (correlation coefficient ranged from 0.77-0.94). Moreover, the chemiluminescence method has been used in several studies to measure ambient NH 3 and has exhibited satisfactory performances (Behera et al, 2010;Meng et al, 2011;Pandolfi et al, 2012). To obtain a finer temporal view of NH 3 variation, the NH 3 data from the ammonia analyzer was used in this study.…”
Section: Sample Analyses and Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at the investigated site, during the cold seasons temperature and relative humidity were of 5.3 ± 3.9 °C and, respectively, (65.3 ± 12.8) % and, according with details presented in Table 4, the (NO 3 -, NH 4 + (total)) pair presented significant correlation (with Pearson coefficient of 0.98, p < 0.001, at the 99.9 % confidence level) only during the cold seasons (low temperature and high relative humidity being favourable for particulate NH 4 NO 3 formation, Stelson and Seinfeld, (1982)). During the warm 25 seasons (temperature and relative humidity of 18.9 ± 3.8 °C and, respectively, 40.5 ± 7.7 %) the (NO 3 -, NH 4 + (total)) pair correlation is of very poor significance most probably due to the influence of meteorological conditions which were not favourable for particulate NH 4 NO 3 formation (increasing temperature and decreasing relative humidity limit the production of NH 4 NO 3 aerosol (Matsumoto and Tanaka 1996;Utsunomiya and Wakamatsu 1996;Alastuey et al 2004) (by an irreversible reaction due to H 2 SO 4 affinity for NH 3 ), known to be as high as 1.5 × 10 -4 sec -1 (Harrison and Kitto, 1992), is almost similar with the reaction rate constants for NH 4 NO 3 formation (by a balanced reaction due to NH 3 affinity for HNO 3 ), which is of the order of 1.59 × 10 -4 m 3 µmoL -1 s -1 (Pandolfi et al, 2012;Behera et al, 2013 and NH 4 NO 3 will be formed via reactions R1 (Cziczo et al, 1997;Zhang et al, 2015) and R2 (Fountoukis and Nenes, 2007;Zhang et al, 2015), (Utsunomiya and Wakamatsu, 1996) and, moreover, NH 4 NO 3 will form only when available excess NH 3 will react with HNO 3 . Backes et al (2016), from their modelling study, suggest that a reduction of NH 3 emissions by 50 % may lead to a 24 % reduction of the total PM 2.5 concentrations in northwest Europe, with the reduction mainly driven by reduced formation of NH 4 NO 3 .…”
mentioning
confidence: 58%